2021
DOI: 10.1097/gox.0000000000003690
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgeons Nationwide Share Experience Regarding Telemedicine in Initial Patient Screening and Routine Postoperative Visits

Abstract: Summary: Physicians attempted to continue providing patient care through the SARS-CoV2 (COVID-19) pandemic. Surgeons embraced telemedicine as patient evaluation transitioned from physical encounters to virtual appointments. However, there is a paucity in the literature on the utility of telemedicine within plastic surgery or how it can meet patients’ needs. A survey study was created to assess surgeons’ involvement and experience with telemedicine. Subjective experience was assessed on a five-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…17 However, the plastic surgeons in the study by Calderon et al reported that they will continue using telemedicine primarily for initial preoperative screening, routine postoperative follow-up, and unscheduled postoperative visits. 9 About half (46.3%) of our respondents worked in the private sector alone when elective procedures were paused, putting them under financial strain. Al Saud et al (2020) reported that 45.7% of the plastic surgeons in their study expressed their apprehension about the financial implications consequent to the restrictions.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…17 However, the plastic surgeons in the study by Calderon et al reported that they will continue using telemedicine primarily for initial preoperative screening, routine postoperative follow-up, and unscheduled postoperative visits. 9 About half (46.3%) of our respondents worked in the private sector alone when elective procedures were paused, putting them under financial strain. Al Saud et al (2020) reported that 45.7% of the plastic surgeons in their study expressed their apprehension about the financial implications consequent to the restrictions.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, personal security and patient privacy cannot be guaranteed with the expanded usage of technology. 2,4,9,[12][13][14][15][16] That said, we believe that telemedicine practice will only grow among plastic surgeons in the post-pandemic era. Our data show that 46.6% of those who did not incorporate telemedicine in their practice during lockdown and 90.6% of those who used telemedicine think that its practice will continue to be an asset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations